Using herbaria to study global environmental change. Issue 1 (30th August 2018) - Lang, Patricia L. M.; Willems, Franziska M.; Scheepens, J. F.; Burbano, Hernán A.; Bossdorf, Oliver
Summary: During the last centuries, humans have transformed global ecosystems. With their temporal dimension, herbaria provide the otherwise scarce long‐term data crucial for tracking ecological and evolutionary changes over this period of intense global change. The sheer size of herbaria, together with their increasing digitization and the possibility of sequencing DNA from the preserved plant material, makes them invaluable resources for understanding ecological and evolutionary species' responses to global environmental change. Following the chronology of global change, we highlight how herbaria can inform about long‐term effects on plants of at least four of the main drivers of global change: pollution, habitat change, climate change and invasive species. We summarize how herbarium specimens so far have been used in global change research, discuss future opportunities and challenges posed by the nature of these data, and advocate for an intensified use of these 'windows into the past' for global change research and beyond.